SPANNING BRIDGES BETWEEN THEORY AND PRACTICE: TERMINOLOGY WORKFLOW IN THE LEGAL AND ADMINISTRATIVE DOMAIN - CHIOCCHETTI, Elena; RALLI, Natascia; LUŠICKY, Vesna; WISSIK, Tanja (Comparative Legilinguistics, 2013)
The purpose of this paper is to illustrate the workflow for the elaboration of multilingual terminology in the legal and administrative domain. Next to giving a short overview over each single step in the workflow, we focus on two important aspects that make multilingual terminology work in the legal domain so challenging and partly different from multilingual terminology work in other domains: the micro-comparative approach and the strong involvement of domain experts. Finally, we discuss a series of practical aspects that distinguish work in the legal domain from terminology work in other domains and partly even clash against some of the requirements set by general terminology theory and practice.